Dinamika Perkembangan Politik dan Hukum Islam Pada Masa Kekhalifahan Turki Usmani dibawah Kekuasaan Sultan Muhammad Al-Fatih - Fajrianti, Farida Hanum; Hasibuan, Intan Delima; Munthe, Fara Salsabila; Wardani, Sri Kusuma; Ilham, Muhammad (Tabayyun : Journal Of Islamic Studies, 2024)
This research aims to examine the dynamics of the development of Islamic politics and law during the reign of Sultan Muhammad al-Fatih in the Ottoman Caliphate. Sultan Muhammad al-Fatih, who ruled from 1451 to 1481, is known as the leader who succeeded in conquering Constantinople in 1453, an event that marked the end of the Byzantine Empire and the beginning of a new era in Islamic and world history. The research method used is in-depth historical analysis of primary and secondary sources, including Ottoman chronicles, legal documents, and notes of contemporary historians. The research results show that under the leadership of Sultan Muhammad al-Fatih, there was a significant transformation in the political and legal structure of the Ottoman Caliphate. Political reforms included the centralization of power and strengthening the state bureaucracy, while in the legal field, Sultan Muhammad al-Fatih implemented a more systematic legal codification and introduced a number of new laws that strengthened the application of Sharia. In addition, the Sultan also promoted religious tolerance and integration of non-Muslim communities within the Ottoman legal framework